The Analysis of Project Finance: a Case Study of Kazakhstan Caspian Transportation System Project - Serikbayeva, Aigul (2011)
Although project finance is a large and fast growing field in finance, there has been very little academic research in that area. The main reason for this deficit is that it is a relatively new sphere in finance and it is difficult to access the information about the implementation of projects from the companies that implement them. This project will provide an overview of how companies finance large infrastructure projects through a case study of the Kazakhstan Caspian Transportation System (KCTS) project. The project will elucidate the current situation in project finance in the oil sector of Kazakhstan; the risks and considerations related to the implementation of large infrastructure projects in emerging markets and recommendations on how to approach the financing and structuring of the KCTS project. The KCTS project has a strategic importance for Kazakhstan as it will create a single energy transportation corridor from Asia to Europe towards the Mediterranean Sea allowing diversification of Kazakhstan export routes for oil thus securing substantial economic benefits. The key feature of the KCTS project is its strong linkage with the Kashagan oil field and transportation systems including an international oil pipeline Baku-Tbilisi-Ceyhan. In addition, the KCTS project’s sponsors are national companies of Kazakhstan and Azerbaijan. Therefore, it is important to consider the issues that should be addressed before the financing can be finalised: acknowledge the interdependency between all participants of the Trans-Caspian Transportation system; ensure guarantees of oil volumes shipped through the KCTS; address all the risks of the project; consider the possibility of participation of shippers in equity stakes and arrange additional funds for any contingencies. The financing structure of the project depends on several aspects inherent in the project: risks, political issues, the stance of the sponsor company, the current situation in world financial markets and the financial and political situation in a host country and the linkage of the infrastructure project with other stakeholders.